Electrode plate, manufacturing method thereof and battery

By using a base coat formed by homogeneously mixed PTC material and adhesive in the electrode sheet, and a self-supporting diaphragm composed of a three-dimensional mesh fiber matrix and an electrode active material, the problems of low production efficiency and poor safety of the electrode sheet are solved, and efficient preparation, overcurrent protection and battery safety are improved.

CN119833539APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311825276.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The production efficiency of electrode sheets is low and the safety is poor, especially when using PTC materials, which requires additional coating and coating processes, which increase process complexity and reduced battery energy density, while also having the risk of thermal runaway.

Method used

The electrode plate design is adopted including a current collector, a basecoat and a self-supporting diaphragm. The basecoat is composed of a homogeneously mixed PTC material and an adhesive. The self-supporting diaphragm is composed of a three-dimensional mesh fiber matrix and an electrode active material. It is prepared by a dry process to achieve bonding and protection while reducing the complexity of the electrode assembly and process.

Benefits of technology

The preparation efficiency of electrode plates is improved, overcurrent protection and energy density are improved. At the same time, due to the obvious boundaries of each layer, the protective effect of PTC material is enhanced, and the circuit can be automatically opened when thermally runaway, improving the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833539A_ABST
    Figure CN119833539A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode plate, a manufacturing method thereof and a battery. The electrode plate comprises a current collector, a bottom coating and a self-supporting diaphragm, wherein the bottom coating comprises a PTC material and an adhesive which are uniformly mixed, and the bottom coating is arranged on the current collector; the self-supporting membrane comprises a three-dimensional net-shaped fiber matrix and an electrode active material, at least part of the electrode active material is connected with the fiber matrix, and the self-supporting membrane is arranged on the bottom coating. The pole piece is realized through a novel dry process, and in the preparation process of the dry process, a layer of conductive adhesive needs to be coated on the current collector, and the self-supporting diaphragm and the current collector are bonded together. The PTC material (positive temperature coefficient material) is added into the conductive adhesive, so that the bonding and protection effects can be realized at the same time, an electrode assembly and tedious procedures do not need to be added, the preparation efficiency is greatly improved, and the overcurrent protection of the electrode plate is realized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode plate and a manufacturing method thereof, and a battery. Background Art

[0002] Since the resistance of conductive composite materials with positive temperature coefficient (PTC) characteristics is sensitive to temperature changes, they can be used as materials for current sensing elements and are currently widely used in overcurrent protection elements or circuit elements. The resistance of PTC conductive composite materials can be maintained at an extremely low value at normal temperature, allowing the circuit or battery to operate normally. However, when an overcurrent or overtemperature occurs in a circuit or battery, its resistance value will instantly increase to a high resistance state (at least 104Ω or more), which is called a trip, and the excess current will be reversed to offset the excess current to protect the battery or circuit element.

[0003] When such PTC materials are applied in electrodes, it is usually necessary to specially coat or prime a thin PTC layer on the adhesive layer. This process will add additional manufacturing processes, resulting in lower manufacturing efficiency of the electrode plates. In addition, the separate PTC thin layer increases the electrode composition and increases the mass proportion of inactive materials, resulting in lower battery energy density. Moreover, when traditional electrode plates use PTC material coatings to block the current collector and electrode materials, the electrode slurry has a certain fluidity and will flow into the coating through the pores of the PTC layer, and it is impossible to achieve complete isolation. Therefore, there is still a certain risk when the battery has thermal runaway. Summary of the invention

[0004] The purpose of this application is to provide an electrode plate and a manufacturing method thereof, and a battery to solve the problems of low manufacturing efficiency and poor safety of the electrode plate.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present invention provides an electrode plate, comprising a current collector, a base coating and a self-supporting film; wherein the base coating comprises a homogeneously mixed PTC material and an adhesive, and the base coating is arranged on the current collector; the self-supporting film comprises a fiber matrix and an electrode active material in a three-dimensional network, at least part of the electrode active material is connected to the fiber matrix, and the self-supporting film is arranged on the base coating.

[0007] In one embodiment, the PTC material includes inorganic nanoparticles and / or polymer materials; when the PTC material includes the inorganic nanoparticles and the polymer material, the mass proportions of the inorganic nanoparticles and the polymer material in the PTC material are 10% to 20% and 80% to 90%, respectively.

[0008] In one embodiment, the inorganic nanoparticles include one or more of strontium titanate, barium titanate, and lead titanate.

[0009] In one embodiment, the polymer material includes one or more of polypyrrole, polyaniline, polystyrene sulfonic acid, high-density polyethylene, polyethylene oxide, alkyl-substituted pyrrole, alkyl-substituted thiophene and polyimide.

[0010] In one embodiment, the primer layer further includes a first conductive agent, and the mass proportions of the PTC material, the adhesive and the first conductive agent in the primer layer are 50% to 97%, 2% to 40% and 1% to 10% respectively.

[0011] In one embodiment, the material for preparing the fiber matrix includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and carboxymethyl cellulose.

[0012] In one embodiment, the thickness of the primer layer is 2 μm to 30 μm.

[0013] In one embodiment, the self-supporting membrane further includes a second conductive agent, and the mass proportions of the fiber matrix and the second conductive agent in the self-supporting membrane are 1% to 10% and 0.2% to 3% respectively.

[0014] In one embodiment, the bulk density of the material for preparing the fiber matrix is ​​0.1kg / L to 0.6kg / L, and / or the average particle size Dv50 of the material for preparing the fiber matrix is ​​0.1mm to 3mm, and / or the molecular weight of the material for preparing the fiber matrix is ​​200w to 800w.

[0015] In a second aspect, the present invention also provides a method for manufacturing an electrode pole piece, comprising: mixing the precursors of the electrode active material and the fiber matrix, fiberizing the precursors to form a self-supporting membrane; mixing the PTC material and the adhesive to obtain a coating slurry, applying the coating slurry on the current collector to form a primer layer; and disposing the self-supporting membrane on the primer layer to obtain the electrode pole piece.

[0016] In the third aspect, the present invention also provides a battery, comprising a diaphragm and the electrode plate described in the first aspect, or an electrode plate prepared by the electrode plate manufacturing method as described in the second aspect, wherein the electrode plate is a positive electrode plate and / or a negative electrode plate, and the positive electrode plate and the negative electrode plate are respectively arranged on opposite sides of the diaphragm.

[0017] The electrode plate provided by the present invention is prepared by mixing a PTC material and an adhesive, and then coating the mixture on a current collector to form a primer layer, so that the original PTC layer and the adhesive layer can form a coating layer, which can achieve both bonding and protection effects without adding electrode components and complicated processes, greatly improving the preparation efficiency, and achieving overcurrent protection of the electrode plate and improving the energy density of the electrode plate at the same time; and the electrode active material in the self-supporting membrane is independent of the primer layer, so that the electrode active material will not penetrate through the primer layer, and the boundaries between the current collector, the primer layer and the electrode active material layers are obvious and completely separated, so that the PTC material can better play a protective role on the battery, automatically cut off the circuit in the event of thermal runaway, and make the battery safer. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 is a cross-sectional schematic diagram of an electrode sheet of an embodiment;

[0020] Figure 2 is a cross-sectional electron microscope image of an electrode sheet of an embodiment;

[0021] Figure 3 This is a cross-sectional electron microscope image of an existing electrode sheet of an embodiment;

[0022] Figure 4 1. The appearance diagram (a) and electron microscope diagram (b) of a self-supporting membrane of an embodiment;

[0023] Figure 5 It is a battery test data diagram of Examples 1-5 and Comparative Examples 1-4;

[0024] Figure 6 It is a battery test data chart of Examples 1-2 and Comparative Example 4.

[0025] Explanation of reference numerals: 100 - electrode plate, 10 - current collector, 20 - bottom coating, 30 - self-supporting membrane, 30A - fiber matrix, 30B - electrode active material DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0027] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0028] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0029] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0030] The present invention provides a new type of electrode plate capable of self-protection. The electrode plate is realized by a new type of dry process. During the preparation process of the dry process, a layer of conductive glue needs to be coated on the current collector to bond the self-supporting membrane to the current collector. PTC material (positive temperature coefficient material) is added to the conductive glue to achieve bonding and protection at the same time, without adding electrode components and cumbersome processes, greatly improving the preparation efficiency, and realizing overcurrent protection of the electrode plate.

[0031] In one implementation, please refer to Figure 1 and Figure 2 The electrode plate 100 includes a current collector 10, a primer layer 20 (the conductive glue mentioned above) and a self-supporting film 30. The primer layer 20 includes a homogeneously mixed PTC material and an adhesive, and the primer layer 20 is disposed on the current collector 10; the self-supporting film 30 includes a fiber matrix 30A and an electrode active material 30B in a three-dimensional network, at least part of the electrode active material 30B is connected to the fiber matrix 30A, and the self-supporting film 30 is disposed on the primer layer 20.

[0032] Specifically, the electrode plate 100 may be a positive electrode plate or a negative electrode plate. The electrode active material 30B in the positive electrode plate is the positive electrode active material, and the electrode active material 30B in the negative electrode plate is the negative electrode active material.

[0033] Optionally, the current collector 10 may be a foam metal mesh, a metal film material, etc., specifically including any one of copper foil and aluminum foil.

[0034] Optionally, the PTC material includes inorganic nanoparticles and / or polymer materials. The inorganic nanoparticles include one or more of strontium titanate, barium titanate and lead titanate. The polymer material includes one or more of polypyrrole, polyaniline, polystyrene sulfonic acid, high-density polyethylene, polyethylene oxide, alkyl-substituted pyrrole, alkyl-substituted thiophene and polyimide.

[0035] Optionally, the adhesive includes one or more of polytetrafluoroethylene and its copolymers, polyvinylidene fluoride and its copolymers, polyolefins and their copolymers, polyethers and their copolymers, polyphenylene ethers and their copolymers, polysiloxanes and their copolymers, polyesters and their copolymers, polyethylene oxide, polyethylene-polyethylene glycol block copolymers, polydimethylsiloxane, poly(dimethylsiloxane-co-alkylmethylsiloxane), nitrile rubber, polyvinyl ester, polyvinyl acetate, and polyacrylate.

[0036] Specifically, the polyolefin includes one or more of polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / vinylidene fluoride copolymer, and propylene / vinylidene fluoride copolymer; polytetrafluoroethylene and its copolymers can be one or more of tetrafluoroethylene / ethylene copolymer, tetrafluoroethylene / propylene copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, tetrafluoroethylene / ether copolymer, tetrafluoroethylene / siloxane copolymer, tetrafluoroethylene / branched polyether copolymer, tetrafluoroethylene / vinyl ether copolymer, and tetrafluoroethylene / branched polyether / vinyl ether copolymer.

[0037] It can be understood that the homogeneously mixed PTC material and adhesive are mixed together to form a mixed slurry when preparing the slurry of the base coating 20. Then, the mixed slurry is coated on the current collector 10 to form the base coating 20.

[0038] Homogeneous mixing refers to a mixture in which the constituent substances are uniformly distributed at the microscopic level, and there are no obvious boundaries between the molecules or ions of different components.

[0039] In existing technologies, PTC materials and adhesives are coated separately, that is, an additional layer of PTC material is added to the electrode plate. On the one hand, this method occupies the mass and volume of the electrode plate, reducing the energy density of the system. On the other hand, the contact impedance between multiple layers of different materials will greatly affect the battery performance.

[0040] In the present invention, a new electrode preparation process is used to directly add the PTC material into the adhesive, thereby reducing the independent PTC material layer, effectively improving the electrode preparation efficiency, reducing the contact impedance between the membrane and the current collector 10, and improving the electrical performance of the electrode.

[0041] Furthermore, the self-supporting membrane 30 is a solid membrane with a three-dimensional structure, which is different from the electrode active slurry. The self-supporting membrane 30 does not have fluidity after being formed, which is not only convenient for transportation, but also can better fit with the above-mentioned base coating 20. Figure 2 As shown, the upper and lower particle parts in the figure are the self-supporting film 30 , the middle layer is the current collector 10 , and the black shadow between the current collector 10 and the self-supporting film 30 is the base coating 20 .

[0042] like Figure 4 As shown, Figure 4 (a) is a self-supporting membrane, and (b) is a fiber matrix connected to the electrode active material, so that the self-supporting membrane can maintain a structure with a fixed shape.

[0043] Optionally, the material for preparing the fiber matrix 30A includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and carboxymethyl cellulose. The fiber matrix 30A is an adhesive, which can be the same as or different from the adhesive in the above-mentioned primer 20, and is not specifically limited. In a specific embodiment, the material for preparing the fiber matrix 30A can be a composite material containing the above-mentioned materials.

[0044] Different from the traditional wet slurrying process, the self-supporting membrane 30 is made by a dry electrode process. The dry electrode process uses a dry mixing method with high shear force (such as an air flow mill) in the mixing stage to mix the electrode materials evenly. At the same time, the material for preparing the fiber matrix 30A is fiberized to form an interwoven network structure, which bonds and supports the active material and the conductive agent to form a self-supporting film sheet that can be independently transported, and its tensile strength is 0.12Mpa~2Mpa.

[0045] This self-supporting film 30 can be directly bonded to the bottom coating 20 containing the PTC material by hot pressing. Therefore, the boundaries between the layers of the current collector 10, the bottom coating 20 and the self-supporting film 30 are clear and completely separated, which can better play the protective role of PTC on the battery, automatically cut off the circuit in the event of thermal runaway, making the battery safer.

[0046] In addition, since some PTC materials have certain adhesiveness, they can provide certain bonding ability during hot pressing and compounding, and combined with the adhesive in the bottom coating 20, the contact strength between the self-supporting film 30 and the current collector 10 is further improved, the peeling force of the pole piece is improved, and the manufacturing ability of the dry pole piece is optimized.

[0047] Optionally, when the electrode plate is a positive electrode plate, the types of positive electrode active materials include lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions. Taking lithium secondary batteries as an example, the positive electrode active material is selected from LiCoO 2 、LiNiO 2 、LiCo x Ni 1-x O 2 (0≤x≤1), LiCo x Ni 1-x-y Al y O 2 (0≤x≤1, 0≤y≤1), LiMn 2 O 4 、LiFe x Mn y M z O 4 (M is at least one of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn or Mo, 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), Li 1+ x L 1-y-z M y N z O 2 (L, M, N are at least one of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S, B, -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1), LiFePO 4 , Li 3 V 2 (PO 4 ) 3 , Li 3 V 3 (PO 4 ) 3 、LiVPO 4 F. Li 2 CuO 2 , Li 5 FeO 4 , and metal sulfides and oxides such as TiS 2 、V 2 S 3 ,FeS,FeS 2 、LiMS x (M is at least one transition metal element such as Ti, Fe, Ni, Cu, Mo, etc., 1≤x≤2.5), TiO 2 Cr 3 O 8 、V 2 O 5、MnO 2 At least one of the group consisting of the following.

[0048] Optionally, when the electrode plate is a negative electrode plate, the type of negative electrode active material includes one or more of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode and an aluminum negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, etc.; the silicon-based negative electrode may include silicon, silicon carbon, silicon oxygen, silicon metal compounds, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy and a lithium indium alloy.

[0049] It can be understood that the self-supporting film 30 is in a solid state, so after the self-supporting film 30 is made on the bottom coating 20, the self-supporting film 30 will not penetrate downward (bottom coating 20) to the current collector 10. Figure 2 and Figure 3 As shown, Figure 3 The electrode sheet is a non-self-supporting electrode sheet. It can be clearly seen in the figure that the electrode active material crosses the bottom coating 20 and contacts the current collector 10.

[0050] The electrode plate provided by the present invention is prepared by mixing a PTC material and an adhesive, and then coating the mixture on a current collector 10 to form a bottom coating 20, so that the original PTC layer and the adhesive layer can form a coating layer, which can achieve bonding and protection at the same time, does not require the addition of electrode components and complicated processes, greatly improves the preparation efficiency, and achieves overcurrent protection of the electrode plate and improves the energy density of the electrode plate at the same time; and the electrode active material 30B in the self-supporting membrane 30 is independent of the bottom coating 20, so that the electrode active material 30B will not penetrate through the bottom coating 20, and the boundaries between the current collector 10, the bottom coating 20 and the electrode active material 30B are obvious and completely independent, which can better play the protective role of the PTC material on the battery, automatically cut off the circuit in the event of thermal runaway, and make the battery safer.

[0051] In one embodiment, when the PTC material includes inorganic nanoparticles and polymer materials, the mass proportions of inorganic nanoparticles and polymer materials in the PTC material are 10% to 20% and 80% to 90%, respectively. The purpose of adding inorganic nanoparticles is to improve the coating uniformity of the PTC layer to avoid that some areas cannot be completely blocked, affecting the over-temperature protection effect. The PTC material selected by the present invention has the characteristics of good conductivity, high reversibility and thin preparation thickness, which is more conducive to the stability of the battery's electrochemical performance and safety protection capabilities.

[0052] In one embodiment, the primer layer further includes a first conductive agent, and the mass proportions of the PTC material, the adhesive and the first conductive agent in the primer layer are 50% to 97%, 2% to 40% and 1% to 10% respectively.

[0053] Optionally, the first conductive agent may be one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fibers, graphene, and the like.

[0054] Optionally, the mass proportion of the PTC material in the primer layer may be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 97%.

[0055] Optionally, the mass proportion of the adhesive in the primer layer may be, but is not limited to, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%.

[0056] Optionally, the mass proportion of the first conductive agent in the base coating layer may be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0057] In one embodiment, the thickness of the primer layer is 2 μm to 30 μm. Optionally, the thickness of the primer layer can be, but is not limited to, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, or 30 μm.

[0058] In one embodiment, the self-supporting membrane further includes a second conductive agent, and the mass proportions of the fiber matrix and the second conductive agent in the self-supporting membrane are 1% to 10% and 0.2% to 3% respectively.

[0059] Optionally, the second conductive agent may be one or more of acetylene black, Ketjen black, Super-P, carbon nanotubes, carbon nanofibers, activated carbon and graphene. It is understandable that the material of the second conductive agent and the first conductive agent may be the same or different.

[0060] The mass proportion of the fiber matrix in the self-supporting membrane can be but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, and 10%.

[0061] Optionally, the mass proportion of the second conductive agent in the self-supporting film may be but is not limited to 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, or 3%.

[0062] Controlling the mass proportion of the fiber matrix in the self-supporting membrane within the above range can not only control the thickness of the self-supporting membrane, but also ensure the electrochemical performance of the self-supporting membrane. If the mass proportion of the fiber matrix in the self-supporting membrane is less than the above range, the fiber matrix will not be able to effectively support the electrode active material, and the self-supporting membrane will not be stable enough; if the mass proportion of the fiber matrix in the self-supporting membrane is greater than the above range, the fiber matrix content is too large, thereby reducing the proportion of active materials and affecting the electrochemical performance of the self-supporting membrane.

[0063] In one embodiment, the bulk density of the material used to prepare the fiber matrix is ​​0.1kg / L to 0.6kg / L, which may be, but is not limited to, 0.1kg / L, 0.2kg / L, 0.3kg / L, 0.4kg / L, 0.5kg / L, and 0.6kg / L. It is understandable that the bulk density of the fiber matrix material is controlled within the above range in order to ensure that the fiberized mixture is sufficiently fluffy. If the bulk density of the fiber matrix material is less than the above range, the preparation of such material is difficult, the production cost is high, and it is not easy to commercialize; if the bulk density of the fiber matrix material is greater than the above range, the obtained matrix is ​​not fluffy enough, and it is difficult to achieve the required thickness and surface density through a single hot pressing; or the mechanical strength of the self-supporting membrane is reduced after multiple hot pressings.

[0064] In one embodiment, the average particle size Dv50 of the material for preparing the fiber matrix is ​​0.1 mm to 3 mm, which can be but not limited to 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, 0.6 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm. Among them, the meaning of Dv50 is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%, that is, it can be understood as the median particle size or median particle size. The particle size distribution of the fiber matrix material in this particle size range is uniform. During the preparation of the pole piece, the fiber matrix material is subjected to a considerable degree of shear force, and the formed polymer fiber network is evenly distributed, so that the structural stability of the fiber matrix is ​​high.

[0065] In one embodiment, the molecular weight of the material for preparing the fiber matrix is ​​200w-800w. The fiber matrix material within this molecular weight range has higher bonding strength and molecular toughness, and the self-supporting membrane prepared therefrom has better structural strength and better electrochemical performance.

[0066] In one embodiment, the present invention further provides a method for manufacturing an electrode plate, comprising the following steps:

[0067] Step S10, mixing the electrode active material and the precursor of the fiber matrix, fiberizing the precursor, and making a self-supporting membrane.

[0068] Step S20 , mixing the PTC material and the adhesive to obtain a coating slurry, and applying the coating slurry on the current collector to form a primer layer.

[0069] Step S30, disposing the self-supporting film on the base coating layer to obtain an electrode plate.

[0070] Specifically, in step S10, (1) the electrode active material, the conductive agent and the binder (precursor of the fiber matrix) are mixed in a predetermined ratio and placed in a V-type mixer for premixing to make them uniformly mixed. The amount of the binder is 1% to 10%, and the amount of the conductive agent is 0.2% to 3%.

[0071] Then, in step S10, the material is fiberized by adjusting the stirring and mixing equipment, wherein the rotation speed is 100 rpm to 6000 rpm. The dispersed material is rolled by a hot roller to form a self-supporting film, and thinned to the required thickness multiple times. During rolling, the line pressure ranges from 0.1 t / cm to 1 t / cm, and the temperature ranges from 100° C. to 250° C.

[0072] In step S20, a certain amount of PTC material is added when preparing the coating slurry, and the coating is applied to the current collector by wet method to obtain the desired current collector. The coating slurry is mainly composed of positive temperature coefficient material (PTC material), adhesive and conductive agent, wherein the content of PTC material is 50% to 97%, the adhesive and conductive agent account for 2% to 40% and 1% to 10% respectively, the thickness of the current collector is 6μm to 17μm, and the thickness of the primer layer is 2μm to 30μm.

[0073] In one embodiment, the present application further provides a battery, comprising a diaphragm and the electrode sheet described above, wherein the electrode sheet comprises a positive electrode sheet and a negative electrode sheet, and the positive electrode sheet and the negative electrode sheet are respectively arranged on opposite sides of the diaphragm. The present application does not limit the specific type of battery, and both the positive electrode sheet and the negative electrode sheet of the battery can be prepared using the above method.

[0074] The technical solution of the present invention is described in detail below through specific embodiments.

[0075] Example 1

[0076] This embodiment provides an electrode plate, the self-supporting film of the electrode plate is a negative electrode film, and the PTC material in the bottom coating layer includes strontium titanate and polystyrene sulfonic acid. The specific manufacturing method is as follows:

[0077] (1) Graphite, polytetrafluoroethylene (PTFE) (molecular weight 5 million, bulk density 0.2 kg / L, D50 0.3 mm) and carbon black were added to an Eirich EL5 laboratory mixer at a mass ratio of 97:2:1. The Eirich EL5 laboratory mixer was operated to stir at 200 rpm (linear speed of about 2 m / s) for 5 minutes; then increased to 1000 rpm (linear speed of about 10 m / s) for 10 minutes; then increased to 4000 rpm (linear speed of about 40 m / s) for 15 minutes; and then continued to stir at a speed of 200 rpm to cool down to obtain a dry mixed material.

[0078] (2) The dry mixed material was added to a hot roller press at 150° C., with the roller gap set to 100 μm, the pressure to 5 T, and the rotation speed to 10 rpm to obtain a self-supporting membrane.

[0079] (3) Strontium titanate and polystyrene sulfonic acid are mixed at a mass ratio of 1:9 to obtain a PTC material. The PTC material, adhesive (polyacrylate) and conductive agent (conductive carbon black) are fully stirred at a mass ratio of 7:2:1 to obtain a coating slurry. The coating slurry is applied on a foil with a thickness of 10 μm, and after drying, the current collector required for the composite dry film is obtained.

[0080] (4) The self-supporting film obtained in (2) is hot-pressed and laminated on the current collector prepared in (3) to obtain a dry-process negative electrode sheet.

[0081] Example 2

[0082] This embodiment provides an electrode plate, the self-supporting film of the electrode plate is a negative electrode film, and the PTC material in the bottom coating layer includes barium titanate and polypyrrole. The difference between the manufacturing method and the embodiment 1 is:

[0083] (3) Barium titanate and polypyrrole were mixed at a mass ratio of 1:9 to obtain a PTC material. The PTC material, a binder (polyacrylate) and a conductive agent (conductive carbon black) were fully stirred at a mass ratio of 7:2:1 to obtain a coating slurry.

[0084] The remaining steps are the same as those in Example 1.

[0085] Embodiment 3:

[0086] This embodiment provides an electrode plate, the self-supporting film of the electrode plate is a negative electrode film, and the PTC material in the bottom coating layer includes barium titanate and polypyrrole. The difference between the manufacturing method and embodiment 2 is:

[0087] (3) Barium titanate and polypyrrole were mixed at a mass ratio of 1.5:8.5 to obtain a PTC material. The PTC material, a binder (polyacrylate) and a conductive agent (conductive carbon black) were fully stirred at a mass ratio of 7:2:1 to obtain a coating slurry.

[0088] The remaining steps are the same as those in Example 2.

[0089] Embodiment 4:

[0090] This embodiment provides an electrode plate, the self-supporting film of the electrode plate is a negative electrode film, and the PTC material in the bottom coating layer includes barium titanate and polypyrrole. The difference between the manufacturing method and embodiment 2 is:

[0091] (3) Barium titanate and polypyrrole were mixed at a mass ratio of 2:8 to obtain a PTC material. The PTC material, a binder (polyacrylate) and a conductive agent (conductive carbon black) were fully stirred at a mass ratio of 7:2:1 to obtain a coating slurry.

[0092] The remaining steps are the same as those in Example 2.

[0093] Example 5

[0094] This embodiment provides an electrode plate, the self-supporting film of the electrode plate is a positive electrode film, and the PTC material in the bottom coating layer includes strontium titanate and polystyrene sulfonic acid. The difference between the manufacturing method and the embodiment 1 is:

[0095] (1) Lithium iron phosphate, polytetrafluoroethylene (PTFE) (molecular weight 5 million, bulk density 0.2 kg / L, D50 0.3 mm) and carbon black were added to a mixer at a mass ratio of 97:2:1. The mixture was stirred at 200 rpm (linear speed of about 2 m / s) for 5 minutes in an Eirich EL5 laboratory mixer; then the mixture was stirred at 1000 rpm (linear speed of about 10 m / s) for 10 minutes; then the mixture was stirred at 4000 rpm (linear speed of about 40 m / s) for 15 minutes; and then the mixture was stirred at 200 rpm and cooled to obtain a dry mixed material.

[0096] The remaining steps are the same as those in Example 1.

[0097] Comparative Example 1

[0098] This embodiment provides an electrode plate, which is a negative electrode plate. The electrode plate is prepared by a wet process and includes a PTC material layer (strontium titanate and polystyrene sulfonic acid) and a common adhesive layer on the current collector.

[0099] (1) The adhesive (polyacrylate) and the conductive agent (conductive carbon black) are mixed in a mass ratio of 8:2, and N-methylpyrrolidone is used as a solvent. After being fully stirred, the mixture is coated on a foil with a thickness of 10 μm. After drying, a current collector with a common adhesive layer is obtained.

[0100] (2) Strontium titanate and polystyrene sulfonic acid are mixed in a mass ratio of 1:9 to obtain a PTC material. PTC material, adhesive (polyacrylate) and conductive agent (conductive carbon black) are mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone is used as a solvent. After being fully stirred, a coating slurry is obtained. The coating slurry is applied to the foil with a common adhesive layer in (1), and after drying, a current collector of a PTC material layer and a common adhesive layer is obtained.

[0101] (3) Graphite, Super-P, and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was used as a solvent, and stirred for 2 h with a high-speed stirrer to fully mix and obtain a main material slurry;

[0102] (4) The slurry obtained in (3) is coated on the current collector obtained in (2), and dried to obtain an electrode sheet.

[0103] Comparative Example 2

[0104] This embodiment provides an electrode plate, which is a negative electrode plate. The electrode plate is prepared by a dry process and includes a PTC material layer (strontium titanate and polystyrene sulfonic acid) and a common adhesive layer on the current collector. The difference between the manufacturing method and embodiment 1 is that:

[0105] (1) The adhesive (polyacrylate) and the conductive agent (conductive carbon black) are mixed in a mass ratio of 8:2, and N-methylpyrrolidone is used as a solvent. After being fully stirred, the mixture is coated on a foil with a thickness of 10 μm. After drying, a current collector with a common adhesive layer is obtained.

[0106] (2) Strontium titanate and polystyrene sulfonic acid are mixed in a mass ratio of 1:9 to obtain a PTC material. PTC material, adhesive (polyacrylate) and conductive agent (conductive carbon black) are mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone is used as a solvent. After being fully stirred, a coating slurry is obtained. The coating slurry is applied to the foil with a common adhesive layer in (1), and after drying, a current collector of a PTC material layer and a common adhesive layer is obtained.

[0107] (3) Graphite, polytetrafluoroethylene (PTFE) (molecular weight 5 million, bulk density 0.2 kg / L, D50 0.3 mm) and carbon black were added to an Eirich EL5 laboratory mixer at a mass ratio of 97:2:1. The Eirich EL5 laboratory mixer was operated to stir at 200 rpm (linear speed of about 2 m / s) for 5 minutes; then increased to 1000 rpm (linear speed of about 10 m / s) for 10 minutes; then increased to 4000 rpm (linear speed of about 40 m / s) for 15 minutes; and then continued to stir at a speed of 200 rpm to cool down to obtain a dry mixed material.

[0108] (4) The dry mixed material was added to a hot roller press at 150° C., with the roller gap set to 100 μm, the pressure to 5 T, and the rotation speed to 10 rpm to obtain a self-supporting membrane.

[0109] (5) The self-supporting film obtained in (4) is hot-pressed and laminated on the current collector prepared in (2) to obtain a dry-process negative electrode sheet.

[0110] Comparative Example 3

[0111] This embodiment provides an electrode plate, which is a negative electrode plate. The electrode plate is prepared by a wet process, and a primer layer is arranged on the current collector. The PTC material in the primer layer includes strontium titanate and polystyrene sulfonic acid. The difference between the preparation method and comparative example 1 is that:

[0112] (1) Strontium titanate and polystyrene sulfonic acid are mixed at a mass ratio of 1:9 to obtain a PTC material. The PTC material, adhesive (polyacrylate) and conductive agent (conductive carbon black) are fully stirred at a mass ratio of 7:2:1 to obtain a coating slurry. The coating slurry is applied on a foil with a thickness of 10 μm, and the desired current collector is obtained after drying.

[0113] (2) Graphite, Super-P, and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was used as a solvent, and stirred for 2 h with a high-speed stirrer to fully mix and obtain a main material slurry;

[0114] (3) The slurry obtained in (2) is coated on the current collector obtained in (1), and dried to obtain an electrode sheet.

[0115] Comparative Example 4

[0116] This embodiment provides an electrode plate, which is a negative electrode plate, and is prepared by a dry process. No PTC material is added to the primer layer, and the ratio of the adhesive to the conductive agent is 8:2. The difference between the manufacturing method and the embodiment 1 is that:

[0117] (3) The adhesive (polyacrylate) and the conductive agent (conductive carbon black) are mixed in a mass ratio of 8:2, and N-methylpyrrolidone is used as a solvent. After being fully stirred, the mixture is coated on a foil with a thickness of 10 μm. After drying, a current collector with a primer layer is obtained.

[0118] The remaining steps are the same as those in Example 1.

[0119] Test method:

[0120] The electrode sheets of the above-mentioned embodiments and comparative examples are cut into The battery was assembled in a glove box (O 2 <0.1ppm, H2 O<0.1ppm), the model is CR2016 button half-cell. The negative electrode shell, negative electrode plate, diaphragm, lithium plate (or positive electrode plate), nickel foam and positive electrode cover are stacked and assembled in sequence, and an appropriate amount of electrolyte is dripped on both sides of the diaphragm. Finally, a hydraulic sealing machine is used to seal the battery for testing. Then the battery performance test is carried out:

[0121] (1) At room temperature, the button cells assembled in the above-mentioned embodiments and comparative examples were subjected to 100 charge and discharge cycles at 1C, and the battery capacity retention rate was recorded. The results are recorded in Table 1.

[0122] (2) The battery was placed in a constant temperature oven and cycled 10 times at 90°C before returning to room temperature for further cycle testing. The capacity retention rates of the samples in each group were compared. The results are as follows: Figure 6 shown.

[0123] Table 1

[0124] Test items Electrode conductivity (S / cm) Room temperature cycle capacity retention rate Example 1 1.82 94.1% Example 2 1.79 94.0% Example 3 1.75 93.7% Example 4 1.55 92.4% Example 5 0.03 96.0% Comparative Example 1 0.98 85.5% Comparative Example 2 1.22 87.4% Comparative Example 3 1.14 86.8% Comparative Example 4 2.02 98.2%

[0125] As shown in Table 1, there is a slight difference in the conductivity between the dry electrode and the wet electrode. After the introduction of the PTC material, the electrode produced by the dry process has better conductivity. Compared with Comparative Example 4, the conductivity of the dry electrode did not decrease significantly after the addition of the PTC material. The wet process (Comparative Example 1 and Comparative Example 3) has a slightly lower conductivity due to the poor compatibility of the additional PTC with the slurry coating system. Example 5 is a positive dry electrode. Compared with the negative electrode material, the conductivity of the lithium iron phosphate material itself is lower.

[0126] From Table 1 and Figure 5 It can be seen from the comparison that Examples 1 to 5 all show electrical performance stability close to that without PTC material (Comparative Example 4), which shows that electrodes with or without PTC material can work normally at room temperature and have stable electrochemical performance. Among them, Example 5 prepares a positive electrode sheet, which also shows that the solution provided by the present application is universal and can be applied to both positive and negative electrode sheets. However, the wet electrode (Comparative Example 1 and Comparative Example 3) and Comparative Example 2 further increase the impedance of the overall electrode due to the additionally added PTC layer, resulting in a decrease in cycle performance and a low capacity retention rate.

[0127] Depend on Figure 6It can be seen that at 90°C, the capacity of the electrode without PTC material decays rapidly after the first discharge, mainly due to the accelerated volatilization of the electrolyte at high temperature, changes in the internal structure of the battery board, short circuits, etc., which cause the capacity to drop rapidly. The PTC protection electrode described in Examples 1 and 2 can effectively protect the safety of the battery. The resistance polarization generated at high temperature inhibits the electrode reaction, making it difficult to deintercalate lithium ions, and the normal charging and discharging process is difficult to carry out. The ultra-low capacity shows that the PTC pole piece prepared under this dry process can completely block the support membrane and the current collector to prevent thermal runaway. In addition, after the battery ambient temperature returns to room temperature, the electrode has good recovery ability and can be restored to the same electrical performance as the original.

[0128] The positive / negative electrode sheets obtained in the above embodiments and comparative examples are matched with the corresponding traditional wet-process negative / positive electrode sheets (such as the negative electrode sheet in Example 1 matches the corresponding traditional wet-process positive electrode sheet) by rolling and die-cutting, keeping the N / P ratio at 1.12 and the design capacity at 2Ah, and the dry battery cells are made by winding or laminating with the diaphragm, and the pole ears are respectively welded on the positive and negative electrode sheets, and the battery cells are placed in the aluminum-plastic film with pre-punched holes, and the electrolyte is injected and packaged to obtain soft-pack batteries. After 24 hours of immersion, the capacity is divided into components. After completion, the protection ability of each embodiment for the battery cell in thermal runaway is analyzed, and the charging and furnace temperature tests are respectively performed:

[0129] Adjust the soft pack battery SOC to 100%,

[0130] (1) Overcharge test conditions: Charge the battery at a constant current of 1C to 1.5 times the cut-off voltage of the above-mentioned battery, and record the battery status during overcharge. If the battery does not smoke, catch fire or explode during overcharge, it is considered to have passed the test.

[0131] (2) Oven temperature test conditions: Place the above-mentioned battery in an incubator, and heat the incubator from room temperature to 400±2℃ at a rate of 5℃ / min, and keep this temperature for 30 minutes before stopping heating and observing for 1 hour. If the battery does not emit smoke, catch fire or explode, it is considered to have passed. Use a multimeter to record the oven temperature / room temperature impedance of the battery and calculate the resistance ratio, that is, the ratio of the battery's resistance at oven temperature to the resistance at room temperature (25℃).

[0132] The above safety test results are recorded in Table 2; 5 / 5pass in Table 2 means that five batteries participated in the test and five batteries passed the test.

[0133] Table 2

[0134] Test items Overcharge test Furnace temperature test Oven temperature / room temperature resistance ratio Example 1 5 / 5pass 5 / 5pass 4620.6 Example 2 5 / 5pass 5 / 5pass 4412.7 Example 3 5 / 5pass 5 / 5pass 4538.2 Example 4 5 / 5pass 5 / 5pass 4886.3 Example 5 5 / 5pass 5 / 5pass 4599.1 Comparative Example 1 3 / 5pass 2 / 5pass 5334.3 Comparative Example 2 5 / 5pass 5 / 5pass 4328.8 Comparative Example 3 1 / 5pass 1 / 5pass 3600.1 Comparative Example 4 0 / 5pass 0 / 5pass 2.1

[0135] As can be seen from Table 2, all embodiments of the present invention can pass the overcharge and furnace temperature tests, indicating that the PTC material used in the present invention and the given ratio, its resistance will increase sharply with the increase of temperature, preventing internal short circuits caused by melting of the diaphragm, etc., ensuring that the battery will not be thermally runaway, and greatly improving the safety performance. Among them, Example 5 uses the positive electrode sheet prepared by the method provided by the present application. Since the conductivity of the lithium iron phosphate material itself is lower than that of the negative electrode material, the resistance ratio of Example 5 is different from that of Example 1, but Example 5 still shows a lower electrode impedance under room temperature testing. In Comparative Examples 1 and 3, a wet process for composite PTC materials is adopted. Since the slurry will penetrate the PTC protective layer and contact the foil, it cannot effectively protect the battery under the test conditions of the present invention. When there is no PTC material in Comparative Example 4, the safety test cannot be passed. Although Comparative Example 2 can pass the test, the additional coating layer increases the production cost and the electrode impedance at room temperature, which is not conducive to the performance of the battery's electrical performance.

[0136] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0137] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. An electrode plate, characterized in that: include current collector; A primer layer, comprising a homogeneously mixed PTC material and an adhesive, wherein the primer layer is disposed on the current collector; The self-supporting membrane comprises a fiber matrix in a three-dimensional network and an electrode active material, at least part of the electrode active material is connected to the fiber matrix, and the self-supporting membrane is arranged on the base coating layer.

2. The electrode plate according to claim 1, characterized in that: The PTC material includes inorganic nanoparticles and / or polymer materials; When the PTC material includes the inorganic nanoparticles and the polymer material, the mass proportions of the inorganic nanoparticles and the polymer material in the PTC material are 10% to 20% and 80% to 90% respectively.

3. The electrode plate according to claim 2, characterized in that: The inorganic nanoparticles include one or more of strontium titanate, barium titanate and lead titanate.

4. The electrode plate according to claim 2, characterized in that: The polymer material includes one or more of polypyrrole, polyaniline, polystyrene sulfonic acid, high-density polyethylene, polyethylene oxide, alkyl-substituted pyrrole, alkyl-substituted thiophene and polyimide.

5. The electrode plate according to claim 1, characterized in that: The primer layer also includes a first conductive agent, and the mass proportions of the PTC material, the adhesive and the first conductive agent in the primer layer are 50% to 97%, 2% to 40% and 1% to 10% respectively.

6. The electrode plate according to claim 1, characterized in that: The material for preparing the fiber matrix includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber and carboxymethyl cellulose.

7. The electrode plate according to claim 1, characterized in that: The thickness of the primer layer is 2 μm to 30 μm.

8. The electrode plate according to claim 1, characterized in that: The self-supporting film further comprises a second conductive agent, and the mass proportions of the fiber matrix and the second conductive agent in the self-supporting film are 1% to 10% and 0.2% to 3% respectively.

9. The electrode plate according to claim 1, characterized in that: The bulk density of the material for preparing the fiber matrix is ​​0.1kg / L to 0.6kg / L, and / or the average particle size Dv50 of the material for preparing the fiber matrix is ​​0.1mm to 3mm, and / or the molecular weight of the material for preparing the fiber matrix is ​​200w to 800w.

10. A method for manufacturing an electrode plate, characterized in that: include: Mixing the electrode active material and the precursor of the fiber matrix, and fiberizing the precursor to prepare a self-supporting membrane; Mixing a PTC material and an adhesive to obtain a coating slurry, and applying the coating slurry on a current collector to form a primer layer; The self-supporting film is arranged on the base coating layer to obtain the electrode plate.

11. A battery, characterized in that: It comprises a diaphragm and an electrode plate as described in any one of claims 1 to 9, or an electrode plate prepared by the method for making an electrode plate as described in claim 10, wherein the electrode plate is a positive electrode plate and / or a negative electrode plate, and the positive electrode plate and the negative electrode plate are respectively arranged on opposite sides of the diaphragm.